2022
DOI: 10.1002/cam4.5301
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic pathways enriched according to ERG status are associated with biochemical recurrence in Hispanic/Latino patients with prostate cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The grading system for the classification of patients, by the International Society of Urological Pathology in 2014, is a significant independent predictor of both biochemical recurrence and clinical recurrence after RP ( 60 ). In our previous study, we reported that Gleason GG2 and GG4/5 at RP were associated with the risk of BCR, compared to GG1 (p=0.037 and p=0.08, respectively) ( 38 ). We observed here that higher Gleason GG were associated with worse pathology and clinical features, as well as more cases having BCR within 5 years after RP.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The grading system for the classification of patients, by the International Society of Urological Pathology in 2014, is a significant independent predictor of both biochemical recurrence and clinical recurrence after RP ( 60 ). In our previous study, we reported that Gleason GG2 and GG4/5 at RP were associated with the risk of BCR, compared to GG1 (p=0.037 and p=0.08, respectively) ( 38 ). We observed here that higher Gleason GG were associated with worse pathology and clinical features, as well as more cases having BCR within 5 years after RP.…”
Section: Discussionmentioning
confidence: 96%
“…This fragmentation can lead to delays in clinical interventions when patients transition between different health insurers and cancer institutes. Fourth, the small sample size and the inclusion criteria of patients, which focused on localized or regionally advanced PC who underwent RP [and with available tumor and non-tumor tissue samples for the study ( 38 )], might explain the low representation of higher Gleason GG and aggressive cases and may have limited the associations found in the analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human PCa bulk RNAseq data raw FASTQ files was collected from multiple cohorts. GEO accessions: GSE120795 57 , GSE126078 58 , GSE156289 59 , GSE114740, GSE217260, GSE179321 60 , GSE112786 61 , GSE104131 62 , GSE31528 63 , GSE54460 64 , GSE22260 65 , GSE216490 66 ; dbGaP accessions: phs000909.v1.p1 42 , phs000915.v2.p2 3 . The TCGA_PRAD read counts and TPM data were acquired using “recount3” 67 R package.…”
Section: Methodsmentioning
confidence: 99%
“…Eventually 877 high quality samples comprising normal, BPH, tumor, primary, AdPCa, CRPCa, mCRPCa, NEPCa, organoid, PDX (patient-derived xenograft) histology groups were selected and used for HuPSA-based deconvolution analysis. The FASTQ files were collected from multiple cohorts including GSE120795 49 , GSE126078 31 , GSE156289 50 , GSE114740, GSE217260, GSE179321 51 , GSE112786 52 , GSE104131 53 , GSE31528 54 , GSE54460 55 , GSE22260 56 , GSE216490 57 ; dbGaP accessions: phs000909.v1.p1 58 , phs000915.v2.p2 2 . The TCGA_PRAD read counts and TPM data were acquired using “recount3” 59 R package.…”
Section: Methodsmentioning
confidence: 99%